2021
DOI: 10.7150/jca.56397
|View full text |Cite
|
Sign up to set email alerts
|

Integrating pre- and post-treatment Plasma Epstein-Barr Virus DNA levels for better prognostic prediction of Nasopharyngeal Carcinoma

Abstract: Background: Pre-and post-treatment plasma Epstein-Barr virus (EBV) DNA are important biomarkers for the prognosis of nasopharyngeal carcinoma (NPC). This study was performed to determine the prognostic potential of integrating EBV DNA levels in plasma measured pre-treatment (pre-EBV) and 3 months post-treatment (3 m-EBV). Materials and methods: A total of 543 incident non-metastatic NPC patients treated with intensitymodulated radiotherapy, with or without chemotherapy, were reviewed. Patients were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…Secondly, the follow-up period of the subjects in this study was not long enough, which may impact the assessment of the 5-year prognosis. Thirdly, EBV-DNA copies at diagnosis and the end of chemoradiotherapy have been shown to be a strong prognosis predictor of NPC patients [ 33 ]. However, the data of EBV-DNA copies were unavailable during the hospitalization of this series of cases in our hospital, which may affect the models' performance.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the follow-up period of the subjects in this study was not long enough, which may impact the assessment of the 5-year prognosis. Thirdly, EBV-DNA copies at diagnosis and the end of chemoradiotherapy have been shown to be a strong prognosis predictor of NPC patients [ 33 ]. However, the data of EBV-DNA copies were unavailable during the hospitalization of this series of cases in our hospital, which may affect the models' performance.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 41 ] conducted a study to determine plasma EBV DNA levels pre-treatment and post-treatment (3 months-EBV) as an important biomarker in the prognosis of NPC. It was found that integrating EBV DNA data pre-treatment and post-treatment (3 months-EBV) could predict an accurate and prognostic risk level for NPC [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of plasma EBV DNA were detected by a real-time quantitative polymerase chain reaction (PCR) before treatment, using the same method and procedure described in our previous publications [ 24 , 25 ]. All plasma EBV DNA tests were performed at the department of Laboratory Medicine of our hospital.…”
Section: Methodsmentioning
confidence: 99%
“…In this present study, there were 673 male patients with available pre-treatment plasma EBV DNA test records. Referring to our previous researches [ 24 , 25 ], the cutoff value for pre-treatment EBV DNA used to classify patients into low and high groups was 1500 copies/mL.…”
Section: Methodsmentioning
confidence: 99%